Pedagogical training in Professional and Technological Education: analysis of an experience with teachers working in the state public network of Rio Grande do Norte (Research, Society and Development, 2021)
This work aims to present the results of the elaboration and application of a training proposal for teachers who develop their activities within the EPT. This proposal was based on discussions about teacher training, conceptual bases, pedagogical practices and theories, and Active Methodologies, aimed at teaching within the EPT. The qualitative research with a bibliographic approach brought some classic authors who are references in the field of Professional and Technological Education. Therefore, an evaluative questionnaire was used for data collection, appropriating the interviewees' statements and analyzing them in the light of Content Analysis and comparing them to what these authors define about the specificities that teachers must acquire in view of this modality, which is imperative to the understanding and analysis of the problem addressed. Thus, as a result, it can be stated that this training proposal proved to be quite relevant to the school context that encompasses the EPT modality in its curricular structure. With the analysis of the observed results, it was noticed the emergence of reflection and awareness brought about by the discussions arising from this training, and a change in perspectives regarding the EMI modality. It is concluded, therefore, that training in the proposed mold, that is, being based on theories and methodologies based on problematization, critical reflection, allowed a broad vision and provided tools for these professionals to practice in the EPT, offering significant contributions to the practices within the Professional and Technological Education of the participating teachers.